An investigation of the influence of the reduced elasticity modulus on strength of pultruded frp members in bending. Issue 1 (July 2020) - Kuznetsov, Ivan; Salakhutdinov, Marat; Shakirzyanov, Farid; Khaydarovand, Lenar; Aripov, Daler
Abstract: The polymer composite known as Fibre Reinforced Polymer (FRP) has several advantages over conventional materials. It has been slowly incorporated into civil infrastructures, because the general regulations have not yet been officially introduced. Pultruded FRP manufactures have internal standards of organizations and Guidelines. Therefore, the design identifies issues that require clarification. This study presents influence of the reduced elasticity modulus on strength of pultruded FRP members in bending with a symmetrical cross-section. The position of the neutral line and calculation of strength and deflections with and without reduced modulus of elasticity are determined in the study. Comparison of the results of calculations showed that when taking into account the reduced modulus of elasticity, the deformability is reduced by up to 15 %. The significance of the results obtained for the construction industry consists in the possibility of a refined calculation of the flexural pultruded FRP members taking into account the reduced modulus of elasticity in order to effectively use the strength reserves and reducing material consumption.